A century of wealth in America - Wolff, Edward N. (Tantor Audio, 2017)
Understanding wealth in the United States--who has it, how they acquired it, and how they preserve it--is crucial to addressing the economic and political challenges facing the nation. But until now we have had little reliable information. Edward Wolff, one of the world's great experts on the economics of wealth, offers an authoritative account of patterns in the accumulation and distribution of wealth since 1900.